Monoclonal gammopathy of undetermined significance with associated necrotizing myopathy: a case report and review of the literature - Anna Bode; Oscar Borja Montes; Karen SantaCruz; Abu Baker Sheikh (European Journal of Case Reports in Internal Medicine)
Background: Monoclonal gammopathies encompass many types of plasma cell proliferative disorders ranging from benign to malignant. Monoclonal gammopathies that meet diagnostic criteria for monoclonal gammopathies of undetermined significance (MGUS) but with clinical manifestations are now being referred to as monoclonal gammopathies of clinical significance (MGCS). MGUS associated myopathies are a rare form of MGCS. Case description: We present a case of MGUS associated necrotizing myositis. The patient had been previously diagnosed with MGUS and myositis around the same time, but prior testing had not revealed the etiology of the myopathy. Repeat biopsy and work-up revealed a necrotizing myopathy. Discussion: MGUS associated myopathies are rare, with the most common being sporadic late-onset nemaline myopathy (SLONM-MGUS) and amyloid light chain (AL) amyloidosis-associated myopathy. MGUS associated necrotizing myopathy is even rarer. Because this condition is so uncommon, there are no standardized guidelines on how to treat this condition. Some case reports or studies suggest treating the myositis with standard of care for the myositis type without considering the monoclonal gammopathy while other studies have suggested that treating the monoclonal gammopathy would be beneficial in treating the associated clinical syndrome. Conclusion: Our case report of MGUS associated necrotizing myopathy encourages internists to broaden their differential diagnosis of myopathy, increasing awareness of a condition that is still not well understood.